Digital Currency Generation Using Hash Function and Digital Signature (DigCur) - Jafar, Qusay Mohammed (Al-Nahrain Journal of Science, 2019)
This paper proposed a strategy to create a digital currency by producing a list of serial numbers by an authorized organization (Issuer). Each number in the serial numbers list will be merged with  the issuer’s secret key (Sec_key)and then hashed using hash function to produce the issuer hash code (H-code).The issuer hash code will be considered as a digital banknote and then it will be distributed to the payee as a type money. When a person likes to pay (transfer) these digital banknotes to another person, he/she must prove this transaction by his/her privet key using digital signature process. This mechanism needs a third party to control the process of money transaction by checking the validity of the digital signature and who is authorized to own this digital banknote. The third party is the issuer himself (the central bank). For each digital banknote the issuer hash code will be saved in a record without changing to check if this digital banknote is counterfeit or not. The problem of double spending will be solved by swapping the owner identifier immediately after the transaction process. The proposed method aims to produce a digital cryptocurrency to be as alternative to the traditional physical currencies and it will be called as DigCur. According to some tests the proposed method can be considered a good method to take advantage of it instead of other cash applications.